Preliminary evaluation on digestibility and the relation to morphology and water content of Brachiaria spp. and their heritability. (20th February 2015) - Thaikua, Sarayut; Ebina, Masumi; Kouki, Kaori; Inafuku, Masahito; Akamine, Hikaru; Shimoda, Katsuhisa; Suenaga, Kazuhiro; Kawamoto, Yasuhiro
Abstract In vitro dry matter digestibility (IVDMD) is one of the most important traits for grass quality improvement. Analysis of IVDMD in laboratory with a large number of breeding populations is very laborious. The objectives of this study were to evaluate IVDMD of brachiariagrass germplasm as material in breeding program, and also to determine the appropriate selection criteria for high digestibility. IVDMD (pepsin‐cellulase method), morphology traits and water content of 17 genotypes of Brachiaria spp. (B. brizantha, B. decumbens, B. ruziziensis and Brachiaria hybrid) were evaluated at two harvesting times, winter and early summer seasons. The correlations among traits were determined, and their heritability were also estimated. IVDMD ranged from 48.9 to 59.0% in winter, and 42.9 to 54.4% in early summer. Among morphological traits, leaf‐stem index (ratio of leaf width/stem diameter) showed the highest correlation with whole plant IVDMD (r = 0.74) followed by leaf‐shape ratio (leaf width/leaf length; r = 0.72), and leaf water content also highly correlated with whole plant IVDMD (r = 0.79). The broad sense heritability of IVDMD and the related traits of two harvests combination were high with the range of 0.75–0.93. The results demonstrate that leaf‐stem index, leaf‐shape ratio and water content could be the useful selection criteria for the breeding of brachiariagrass for high digestibility.